Boosting catalytic performance in ZSM-5 (50) catalyst cracking: microwave and Taguchi method with nitrogen activation - Sulaiman, Muataz M.; Makki, Hasan F.; Zabar, Muhannad K. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Microwave power has a more significant effect on cracking with less energy consumption. The microwave power and the catalysis increase the racking rate and the conversion at lower temperatures.  Accordingly, the generated hot spots in the catalyst offer a suitable condition for cracking (high rate and low temperature). The microwave technique was used to conduct the cracking of heavy naphtha. A set of experiments was done with microwave power (750–1250 W), preheating temperatures (150–250 ˚C), and space velocities (2–6 l/hr) with and without nitrogen injection. The nitrogen injection enhanced the conversion for all situations. The best result has a conversion of 47.37% with nitrogen injection at microwave power of 1250 W, a flow rate of 4 l/hr, and a preheating temperature of 250˚C. Generally, it was noted that the flow rate did not affect the conversion. Compared to conventional techniques, the microwave power increased both the reaction and conversion rates, allowing for work at lower temperatures that traditional methods cannot achieve. This study investigated how microwaves with catalysts affect residence time, energy savings, and conversion. The microwave technique experiment could be scaled up to become a mass production unit in any refinery.